The potential of Pterocarpus indicus as a revegetation plant for coal mine Reclamation Land - Ratih Wijayanti; Nabila Aprianti; Nazula Nutayla; Hardian Aries Nugraha; Asia Afriyani (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2026)
Coal mining exploitation generally uses open-pit mining techniques that have implications for environmental degradation, particularly changes in the physical, chemical, and biological properties of the soil. Revegetation of reclaimed land is a strategy for restoring ecosystem functions that have been disrupted by mining activities. This study aimed to evaluate the growth potential of Pterocarpus indicus through direct planting methods and to assess the effect of fertiliser type on plant growth acceleration on post-coal mining land. Field observations were used to measure plant growth parameters, including height, stem diameter, and number of leaves. The planting material used was stem cuttings, with variations in fertiliser treatment. Plant material type, fertiliser type, and application dose had a significant effect on plant growth variables (P<0.05). Duncan’s multiple range test indicated that the use of bokashi fertiliser at a dose of 3 kg per planting hole gave the best results, as evidenced by an average plant height of 104.38 cm, an average stem diameter of 37.692 cm, and a total of 21.99 leaves. Therefore, the direct planting method using stem cuttings as planting material with the application of bokashi fertiliser at a dose of 3 kg plays an important role in accelerating vegetation recovery in coal mine reclamation.